A probable case of laboratory-acquired infection with salmonella typhi: evidence from phage typing, antibiograms, and analysis by pulsed-field gel electrophoresis - Thong, Kwai Lin; Cheong, Y.M.; Pang, T. (Elsevier, 1996)
Objective: To report a probable case of laboratory-acquired typhoid fever involving a female laboratory technologist at a major diagnostic bacteriology laboratory in Kuala Lumpur, Malaysia. Methods: The technologist presented with clinical symptoms of typhoid fever and was admitted to a major hospital in Kuala Lumpur. Salmonella typhi isolated from her stools, as well as other S. typhi isolates she had been working with, were analyzed by Vi phage typing, antibiogram studies, and pulsed-field gel electrophoresis. The phage type and antibiograms of the isolate were identical to those of one of the laboratory strains she had been working with during her routine duties. Results: Pulsed-field gel electrophoresis analysis of restricted chromosomal DNA confirmed the identity of the isolate with that of the laboratory isolate. The isolate involved was phage type El and was resistant to multiple antibiotics. Conclusion: The results strongly suggest that the laboratory technologist acquired the infection in the laboratory in the course of her work.